The liability Resulting from Nullity of the Arrest of the Accused in Libyan law - Al-Sharif, Abdullah Abdul Salam; Haj Ibrahim, Badruddin (Journal of Economic, Administrative and Legal Sciences, 2019)
This study examines the nature and circumstances of the nullity of the arrest of the accused and the consequent legal responsibility for those who implement it in the Libyan legislation. To arrest someone is one of the most dangerous measures against human freedom and affects one of the most significant human rights: the right to freedom, The study relies on the analytical descriptive approach to describe the legal responsibility resulting from the nullity of the procedures for the arrest of the accused by examining and analyzing the legal provisions and the judicial authorities concerned in the Libyan law, to identify the conditions of the nullity of the arrest and its nature and types and effects on the resulting evidence, as well as an assessment of the position of the Libyan legislature towards the legal responsibility. The findings of this study reveals a number of results, the most important: that there is a clear judicial disorder and a big difference between the explanation of the law on the type and nature of nullity resulting from violation of guarantees of arrest. It also reveals that the crime of unjustified arrest varies depending on its source, as individual arrest made by another individual does not violate the freedom of movement of the individual but rather to violate the right itself. Most of the Arab legislation, including Libyan legislation, has taken the theory that the state is not responsible for the work of the judiciary. The Libyan legislator did not directly state the responsibility of the state for the illegal arrest of the judicial officers, and attributed this to the general rules of responsibility.
Keywords: legal responsibility; nullity; arrest